Effects of Palm Oil Addition on Starch and Dietary Fiber Contents of Parboiled Rice - Gita Addelia Nevara; Cesar Welya Refdi (LPPM Universitas Muhammadiyah Riau, 2019)
The formation of lipids and amylose complex is known to increase the resistance of starch towards digestive enzyme and acts like dietary fiber, thus the effects of palm oil addition during parboiling process on rice starch and dietary fiber contents were examined. High amylose rice grain (IR42) was used as a raw material. Modified parboiled rice prepared by adding different amount of palm oil (i.e 10%, 15% and 20% of total grain) during heating process. The results showed that the treatments affect starch and dietary fiber contents of parboiled rice significantly. The results of this study are expected to contribute in the development of modified rice as an alternative diet to prevent and decrease the number of type 2 diabetics.